Isolation of a Novel Antibacterial Phenyl Thioketone from the Seagrass, Cymodocea serrulata. (14th January 2015) - Gnanambal, K. Mary Elizabeth; Patterson, Jamila; Patterson, Edward J. K.
<x xml:space="preserve">Abstract</x> A total of 40 extract types of varying polarities from commonly occurring seagrasses were tested for their antibacterial efficiency against 14 clinically isolated human pathogens using agar well diffusion technique. The extracts from acetone of Cymodocea serrulata expressed moderate broad span of activity against a range of gram‐positive and gram‐negative isolates that were at least resistant to five of the commercially available antibiotics at a minimal concentration of 10 µg. The active extracts of C. serrulata that showed maximal inhibitions were purified using column chromatography that afforded six compounds (a–f). Compound f elicited pronounced inhibitions against Escherichia coli with minimal inhibitory concentration values of 1–3 µg concentration using micro‐dilution method. The active compound was identified as phenyl thioketone using various spectral analyses. This is the first investigation that reveals thioketone functionality from this seagrass species possessing antibacterial actions. This study indicates that there are thiocarbonyl groups from marine floral sources too, which could be possibly used for therapeutic purposes. Copyright © 2015 John Wiley & Sons, Ltd.